2023
DOI: 10.1002/aqc.3998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple stressors on recruitment of long‐lived endangered freshwater mussels

Kazuki Miura,
Nobuo Ishiyama,
Junjiro N. Negishi
et al.

Abstract: Multiple stressors can affect populations interactively. However, the process by which they affect recruitment remains unclear, especially in long‐lived organisms with complex life cycles. This study explored the bottleneck stages of juvenile recruitment in the endangered freshwater pearl mussel Margaritifera togakushiensis and the interactive effects of nutrients and fine sediments on these stages. The proportion of M. togakushiensis juveniles aged ≤10 years was investigated in 24 rivers from north‐eastern Ja… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Under such conditions, a chain of adult abundance decreases in winter, high mortality of gravid mussels and newly born juveniles occurs in summer, and population size decreases with a lack of juveniles at annual or longer timescales. Recent studies have indicated that multiple stressors can limit the community structure, distribution, and reproduction of freshwater species, including freshwater mussels, in complex ways (Birk et al, 2020;Miura et al, 2023a). Our findings extend the multiple-factor paradigm and underscore the importance of considering survival limitation factors acting at multiple life stages of freshwater mussels at different times of the year.…”
Section: Implications For Conservationsupporting
confidence: 71%
See 1 more Smart Citation
“…Under such conditions, a chain of adult abundance decreases in winter, high mortality of gravid mussels and newly born juveniles occurs in summer, and population size decreases with a lack of juveniles at annual or longer timescales. Recent studies have indicated that multiple stressors can limit the community structure, distribution, and reproduction of freshwater species, including freshwater mussels, in complex ways (Birk et al, 2020;Miura et al, 2023a). Our findings extend the multiple-factor paradigm and underscore the importance of considering survival limitation factors acting at multiple life stages of freshwater mussels at different times of the year.…”
Section: Implications For Conservationsupporting
confidence: 71%
“…One of the most prevalent signs of population decline in freshwater mussels is the cessation of their reproduction, which can often be reflected in disproportionately fewer juveniles in population demography and small population sizes (i.e., abundance) (Österling et al, 2010;Negishi & Kayaba, 2010). Efforts have been made to identify how population decline and reproduction cessation occur by examining single or multiple life-history stages of species in relation to various external environmental factors (Geist et al, 2006;Österling et al, 2010;Strayer & Malcom, 2012;Tremblay et al, 2016;Brian et al, 2021;Miura et al, 2023a). Furthermore, as intrinsic properties of mussels, demographics, including size frequency, age structure, sex ratios, and survival rates, are among the key parameters in inferring impaired populations and projecting how and whether the populations would change in the future (Ferreira-Rodríguez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%